Occupational health and safety policy and compliance audit for the sanitation worker in a waste management company - George Mit; Claudiu Babiş; Elena Anda Botoc; Anișoara Habuc; Andrei Dimitescu (Journal of Research and Innovation for Sustainable Society)
As part of our ongoing concern for the safety and well-being of our employees, CleanCity Services has decided to conduct an exhaustive occupational health and safety compliance audit. The purpose of this audit is to assess and ensure compliance with the highest OH&S standards and regulations, and to identify opportunities to improve our existing practices and procedures. In this audit, we will focus on assessing our compliance with applicable laws and regulations, the validity and updating of OSH documentation, the identification and proper management of occupational risks, the effectiveness of our OSH policies and procedures, as well as identifying opportunities to improve our system of occupational health and safety management.